Condom Effectiveness for HIV Prevention by Consistency of Use Among Men Who Have Sex With Men in the United States. (1st March 2015) - Smith, Dawn K.; Herbst, Jeffrey H.; Zhang, Xinjiang; Rose, Charles E.
Abstract : Objective: We derived an estimate of male condom effectiveness during anal sex among men who have sex with men (MSM) because the most widely used estimate of condom effectiveness (80%) was based on studies of persons during heterosexual sex with an HIV-positive partner. Design: Assessed male condom effectiveness during anal sex between MSM in 2 prospective cohort studies of HIV incidence by self-reported consistency of use. Methods: Analyzed data combined from US participants in the EXPLORE trial (1999–2001) public use data set and in the VAX 004 trial (1998–1999) data set. Initially, HIV-uninfected MSM enrolled in these trials completed baseline and semiannual interviews about their sexual behaviors with male partners and underwent HIV testing. Using a time-to-event model, effectiveness of consistent condom use in preventing HIV infection was estimated among men reporting receptive and/or insertive anal sex with an HIV-positive partner and consistency of condom use. Results: Among MSM reporting any anal sex with an HIV-positive male partner, we found 70% effectiveness with reported consistent condom use (compared with never use) and no significant protection when comparing sometimes use to never use. This point estimate for MSM was less than the 80% effectiveness estimate reported for heterosexuals in HIV-discordant couples reporting consistent condom use. However, the point estimates in the 2 populations are not statistically different. Only 16% of MSM reported consistent condom use during anal sex with male partners of any HIV status over the entire observation period. Conclusions: These estimates are useful for counseling efforts and for modeling the impact and comparative effectiveness of condoms and other prevention methods used by MSM. Abstract : Supplemental Digital Content is Available in the Text.